Recent Microwave Technologies - Kishk, Ahmed; Ho Yeap, Kim (IntechOpen, 2022)
Microwave bands range from 300 MHz to 300 GHz of the electromagnetic spectrum. These signals can be used in communication, networking, astronomy, and biomedical engineering, among other fields. This book provides a comprehensive overview of the physics of microwave signals, techniques for modeling these signals, uses of these signals in various fields, and the underlying principles of some of the latest microwave devices currently available.